A delicate method for the synthesis of high-efficiency Hg (II) The adsorbents based on biochar from corn straw biogas residue. (25th June 2022) - Qian, Xin; Wang, Ruixue; Zhang, Quanguo; Sun, Yong; Li, Wenzhe; Zhang, Lingling; Qu, Bin
Abstract: The valorisation of biogas residue from agricultural waste is challenging. Herein, the biochar from corn straw biogas residue is prepared by modifying with KOH and applied for removing of Hg (II) from wastewater to achieve the full quantification of agricultural residue waste. Scanning electron microscopy (SEM) results show that the corn straw biogas residue biochar (BRB-1) has abundant microporous, mesoporous and the layered structure, similar to graphene. The biochar has a high surface area (754.45 m 2 /g) according to the result of the N2 adsorption-desorption experiments. The adsorption kinetics were in accordance with pseudo-second-order kinetic, which is a chemisorption-dominated adsorption process. The adsorption isotherms were consistent with the Langmuir model with the optimum adsorption amount of 269.08 mg/g, indicating that the adsorption process was a single molecular layer chemisorption. Furthermore, the XPS and FTIR results indicated that the abundant oxygen-containing functional groups can be found in BRB-1, which play an important role in the adsorption of Hg (II). Therefore, BRB-1 has an excellent adsorption capacity for Hg (II) and possesses good application prospects in the treatment of Hg (II) polluted wastewater. Graphical abstract: Image 1 Highlights: Biochar was prepared from Corn straw biogas residue by KOH chemical activation. Digestion expanded the specific surface area and pore size of the corn straw. Modified biochar had a high adsorption efficiency adsorption for the removal Hg (II). Preliminary exploration of the reduction mechanism in the adsorption of Hg (II).